2022
DOI: 10.3389/fspor.2022.823488
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Safety in High-Performance Sport: Contextually Applicable?

Abstract: In recent years, high-performance sport has seen a rising interest in Psychological Safety, a construct with a strong empirical basis in certain business contexts. As research and practice interest grows in PS, there are early indications of practitioners and, to a lesser extent research, treating the construct as being universally transferable. We offer three central concerns with this situation. Firstly, it seems that a variety of different interpretations in use may limit the practical application of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…In line with recent critiques of the uncritical application of PS as a conceptual model in HP sport, data in this study suggest a complex and nuanced relationship between perceptions of safety and performance development [14]. Much like data collected in other contexts, it does appear that the construct may not always be a performance enhancer [15].…”
Section: Psychological Safetysupporting
confidence: 74%
See 4 more Smart Citations
“…In line with recent critiques of the uncritical application of PS as a conceptual model in HP sport, data in this study suggest a complex and nuanced relationship between perceptions of safety and performance development [14]. Much like data collected in other contexts, it does appear that the construct may not always be a performance enhancer [15].…”
Section: Psychological Safetysupporting
confidence: 74%
“…Several issues with the application of the construct in HP have been raised. As highlighted in a recent critical review, even by redefining the construct, it is difficult to see how it can be applied to athletes in HP [14]. At the very least, it has been suggested that there is a need to apply PS in a critical manner, understanding potential downsides such as lower overall performance without accountability, or even unethical behaviour [15,16].…”
Section: Psychological Safetymentioning
confidence: 99%
See 3 more Smart Citations